Kingdom of Eswatini : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of Eswatini. (IMF Staff Country Reports; Country Report, 2020)
This 2019 Article IV Consultation with the Kingdom of Eswatini highlights that the financial system remains sound, although vulnerabilities are rising. Hence, bank supervision should be intensified, the early intervention regime strengthened, and plans to relax single borrower concentration regulations suspended. The paper explains that the authorities have recently taken some policy actions toward stabilizing the economy. However, reflecting expansionary spending policies and declining Southern African Customs Union revenue, public debt is still rising, domestic arrears have accumulated, and international reserves have fallen below adequate levels. Supply side and governance reforms are needed to support private investment and strengthen competitiveness. Reforms should reduce vulnerabilities to state-capture and other forms of corruption, streamline business regulations and regulatory requirements, reduce high electricity and telecommunications costs, contain wage growth, and address shortages of skilled workers. A credible medium-term fiscal adjustment plan, starting with measures to reduce next year's fiscal deficit, is needed to bring the economy on a sustainable path. Policies should combine expenditure reductions and revenue increases that enhance long-term growth prospects. Expanding and better targeting cash transfers would help protect the poor.